2011
DOI: 10.3832/ifor0558-004
|View full text |Cite
|
Sign up to set email alerts
|

A review of the environmental Kuznets curve hypothesis for deforestation policy in Bangladesh

Abstract: Deforestation in the tropical developing countries is the critical environmental concern to ecologists and environmentalists. Environmental Kuznets Curve (EKC) hypothesis is critical to understanding the development path of a nation in relevance to its environment. The dictation of national economic growth to deforestation can be found through the study of EKC. To understand the EKC phenomena for deforestation, the study was undertaken through reviewing the literature. With the understanding of the different E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…The hypothetic analysis of deforestation and growth indicators have mainly been focused on cross-country and panel-data approaches. However, recently, after recognizing the environmental issues, there are some developing countries that have been studied using the EKC hypothesis (Miah et al, 2011;Naito and Traesupap, 2014) on Bangladesh and Thailand, respectively.…”
Section: Methodology and Model Specificationmentioning
confidence: 99%
“…The hypothetic analysis of deforestation and growth indicators have mainly been focused on cross-country and panel-data approaches. However, recently, after recognizing the environmental issues, there are some developing countries that have been studied using the EKC hypothesis (Miah et al, 2011;Naito and Traesupap, 2014) on Bangladesh and Thailand, respectively.…”
Section: Methodology and Model Specificationmentioning
confidence: 99%
“…Deforestation, a major phenomenon of environmental degradation is a product of national economic growth 83) . Studies found that national economic growth affects tropical deforestation 84,85) .…”
Section: Analysis Of Causes and Underlying Forces Of Environmental De...mentioning
confidence: 99%
“…Furthermore, widespread corruption and poor governance in the forestry sector (Muhammed et al, 2008) is hindering the progress of social forestry programs. In addition to eliminated corruption, Miah et al (2011) suggest greater political will is needed to support community forestry, as well as initiatives that bridge the gap between policy, science, and practice. They also note many regulatory policies and measures are too vague to be of much use, creating loopholes that lead to abuse.…”
Section: Co-management (Ipac) Project Supported By Usaid (United Statesmentioning
confidence: 99%